Cell biology of hydrogels - Smetana, K (Biomaterials, 1993)
This paper demonstrates the hydrophilic polymers (mainly based on hydroxyethyl methacrylate) as a tool of cell biology. They represent a favourable model for the study of the influence of the molecular design of polymers on (1) bioactive protein adsorption, (2) cell adhesion and/or (3) control of their function. The influence of the hydrophilic/hydrophobic properties of polymers and of the occurrence of charged functional chemical groups is able to influence the interaction of cells with these polymers. For example, the copolymer of hydroxyethyl methacrylate with sodium methacrylate (-COO- groups) is only little recognized by macrophages, which could be used in clinical implantology. It is shown that, similar to natural macromolecules of the extracellular matrix, the synthetic polymers are able to participate in the control of cell function.
Keywords: methakryláty; Humans; proteiny; Extracellular Matrix; Proteins; makrofágy; Microscopy, Electron, Scanning; extracelulární matrix; Cell Adhesion; lidé; zvířata; polymery; Gels; Polymers; Adsorption; mikroskopie elektronová rastrovací; gely; Animals; buněčná adheze; Macrophages; adsorpce; Methacrylates